Trend of electroconvulsive therapy use and its relationships with clinical characteristics from a large psychiatric center in China - Li, Wei; Hu, Na; Gao, Xiaoxiao; Song, Yanying; Zhang, Rongzhen; Sun, Shiyou; Tong, Jinghui; Shen, Yang; Yu, Yongjun; Yang, Kebing; Chen, Yan; Song, Jiaqi (Frontiers in Psychiatry, 2025)
BackgroundRecent studies on electroconvulsive therapy (ECT) have reported inconsistent frequencies of ECT use in various countries. Therefore, this study aimed to investigate the trends of ECT use in a large psychiatric center in China over 6 consecutive years.MethodsA total of 22,120 inpatients, aged 18–59 years, admitted during the period 2015–2020 to a large grade-A tertiary psychiatric center in Beijing were enrolled in this retrospective study. Demographic and clinical data including vital signs; daily living abilities(ADL); emergency referrals; psychiatric and physical prescriptions were collected from an electronic medical records system.ResultsIn all, 2,213 (10.0%) inpatients received ECT, with an average number of sessions of 10.3 ± 6.6. There were no significant differences between the ECT and non-ECT groups in terms of educational level, marital status, length of hospital stay, and blood pressure. After using the propensity score matching (PSM) method, Multiple logistic regression analysis revealed that ECT use was independently associated with married/cohabitating (OR = 1.21, 95% CI: 1.03-1.43); few hospitalizations (OR = 0.96, 95% CI: 0.93-0.99); unemployed (OR = 1.43, 95% CI: 1.16-1.76); emergency referral (OR = 1.62, 95% CI: 1.36-1.93); increased use of antipsychotics (OR = 2.63, 95% CI: 1.88-3.68), mood stabilizers (OR = 1.30, 95% CI: 1.01-1.67), antidepressants (OR = 1.40, 95% CI: 1.13-1.73), and trihexyphenidyl (OR = 1.30, 95% CI: 1.05-1.50); reduced use of hypoglycemic drugs (OR = 0.64, 95% CI: 0.45-0.83); fast heart rate (OR = 1.01, 95% CI: 1.01-1.02); and severe impairments in ADL. Compared with that in 2015 (13.2%), ECT use decreased annually from 2016 (12.4%) to 2019 (9.6%), especially in 2020 (5.7%), given the impact of the COVID-19 pandemic in China.ConclusionsThe ECT usage and year-by-year decrease in ECT use in this study were consistent with the recent trends in other regions. Patients with the married/cohabitating, unemployed, and emergency-referral, unstable vital signs, more severe disability received ECT for quick alleviation of their conditions.